2004
DOI: 10.1007/s00432-003-0518-7
|View full text |Cite
|
Sign up to set email alerts
|

The coexistence of ERBB2, INT2, and CMYC oncogene amplifications and PTEN gene mutations in endometrial carcinoma

Abstract: Our data suggest that differences in the presence of genetic defects may reflect the different molecular pathways of endometrial carcinogenesis. These data also suggest that location of intragenic PTEN mutations and their coexistence with the CMYC amplification may play a crucial part in the development of various subtypes of endometrial carcinoma, but this preliminary suggestion requires further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
2
5
0
Order By: Relevance
“…No mutation has been discovered beyond the regions encoding N-terminal phosphatase and C2 domains. Similar trend in distribution of mutations in PTEN gene was described also in Polish population (65% in N-terminal phosphatase domain, 31.4% in C2 domain) [19, 22], in contrast with the opposite distribution of PTEN gene mutations observed in the study from United States (47% in N-terminal phosphatase domain, 50% in C2 domain) [12–18] and Japan (33% in N-terminal phosphatase domain, 66% in C2 domain) [20, 21]. …”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…No mutation has been discovered beyond the regions encoding N-terminal phosphatase and C2 domains. Similar trend in distribution of mutations in PTEN gene was described also in Polish population (65% in N-terminal phosphatase domain, 31.4% in C2 domain) [19, 22], in contrast with the opposite distribution of PTEN gene mutations observed in the study from United States (47% in N-terminal phosphatase domain, 50% in C2 domain) [12–18] and Japan (33% in N-terminal phosphatase domain, 66% in C2 domain) [20, 21]. …”
Section: Discussionsupporting
confidence: 79%
“…It was previously reported that mutations occurring in PTEN exons encoding the phosphatase domain cause complete loss of its suppressor function thus leading more rapidly to the development of a more malignant phenotype of endometrial tumors [22]. In our study 59% (23/39) of mutations described were localized in N-terminal phosphatase domain.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…4,18 Besides that, they developed in approximately 20% of endometrial hyperplasia cases and, in consequence, were considered as precursor changes in the development of ECs. 4 In our present and previous studies, 7 we demonstrated PTEN mutations in 48% to 55% of cases of endometrial cancer. These data are in agreement with the reports in the literature, which demonstrate the incidence of PTEN mutations in endometrial cancers to be approximately 50% on the average and even almost 80%.…”
Section: Discussionsupporting
confidence: 65%
“…Detailed descriptions of PTEN mutations we detected in endometrial cancers are contained in our earlier articles. 7 The locations of PTEN mutations in endometrial cancers are presented in Figure 2.…”
Section: Molecular Resultsmentioning
confidence: 99%